Pengaruh Tingkat Kesehatan Bank dengan Metode RGEC terhadap Corporate Social Responsibility (Studi pada Bank Umum Syariah di Indonesia) Tahun 2019 - 2024 - Anisa Putri Febriyanti; Lucky Enggrani Fitri; Rico Wijaya; Agus Solikhin (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the influence of bank soundness using the Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital (RGEC) methods on Corporate Social Responsibility (CSR) disclosure in Islamic Commercial Banks in Indonesia for the period 2019–2024. Bank soundness is measured through the Non-Performing Financing (NPF) ratio, Return on Assets (ROA), Capital Adequacy Ratio (CAR), and GCG assessment results. Research data were obtained from annual reports, sustainability reports, and official publications of the Financial Services Authority (OJK). The research method used is a quantitative approach with multiple linear regression analysis through classical assumption tests and hypothesis testing. The results show that NPF has a significant negative effect on CSR disclosure, while ROA has a significant positive effect. Meanwhile, GCG and CAR do not have a significant effect on CSR disclosure. This finding indicates that risk and profitability factors are the main determinants of CSR disclosure, while governance and capital aspects have not contributed significantly. This research is expected to enrich the literature on the relationship between bank health and CSR in the Islamic banking sector, as well as serve as a reference for banks in optimizing the implementation of CSR in a sustainable manner.